2017
DOI: 10.2196/resprot.7434
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Nonclinical Factors Associated With 30-Day Readmission in Patients with Cardiovascular Disease: Protocol for an Observational Study

Abstract: Background Cardiovascular disease (CVD) is the leading cause of hospitalization in older adults and high readmission rates have attracted considerable attention as actionable targets to promote efficiency in care and to reduce costs. Despite a plethora of research over the past decade, current strategies to predict readmissions have been largely ineffective and efforts to identify novel clinical predictors have been largely unsuccessful. Objective The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Prior research compared patients enrolled in the study with all eligible patients at Duke Heart Center and showed that the two patient groups had similar demographic and clinical profiles. 27 No compensation was provided to patients who participated in the study. Further details on subject selection, recruitment, and survey administration have been documented elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research compared patients enrolled in the study with all eligible patients at Duke Heart Center and showed that the two patient groups had similar demographic and clinical profiles. 27 No compensation was provided to patients who participated in the study. Further details on subject selection, recruitment, and survey administration have been documented elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Further details on subject selection, recruitment, and survey administration have been documented elsewhere. 27…”
Section: Methodsmentioning
confidence: 99%
“…Details on subject selection, recruitment and survey administration have been documented elsewhere. 19 The final sample for this study included 520 patients for analysis. All subjects provided informed written consent to participate in the study, and the study was approved by the Institutional Review Board at Duke University Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…Other variables, although representing healthcare indicators that may be present in any system, are nonclinical factors, which are little explored in the models available to predict risk for hospital readmission. Thus, there is still little known of the influence that life habits and the support of the health system exert on this occurrence (Dupre et al, 2017).…”
Section: Ta B L E 2 Univariate Analysis For Variables At Intermediate Level For Cardiac Patients Hospital Readmissionmentioning
confidence: 99%